Meckel-Gruber syndrome: about a case identified during deliver - Wade, Mouhamadou; Gueye, Mamour; Mbodji, Aissatou; Ndiaye, Mame D.; Sene, Mouhamed; Mbaye, Magatte (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Meckel-Gruber syndrome is an autosomal recessive disorder, usually lethal, most commonly characterised by the classic triad of polycystic kidneys, occipital encephalocele and polydactyly. Antenatal diagnosis can be made by ultrasound between 10 and 14 weeks of amenorrhoea. Recognition of this syndrome is important in order to establish the diagnosis and provide genetic counselling. Finally, well supervised termination of pregnancy should be the rule for lethal fetal malformations in order to relieve the psychological suffering of patients. However, in certain situations or working conditions, the diagnosis can be made late or even discovered during childbirth. We report a case of Meckel Gruber syndrome discovered at birth.